Small-Scale Milk Processing, Utilization and Marketing of Traditional Dairy Products in Bahir Dar Zuria and Mecha Districts, Northwestern Ethiopia - Seifu, Eyassu; Tassew, Asaminew (Journal of Food Technology Research, 2014)
This study was conducted to assess processing, utilization and marketing of traditional dairy products produced in Bahir Dar Zuria and Mecha districts in Northwestern Ethiopia. A single-visit-multiple-subject formal survey was conducted to collect data. A total of 150 households (75 households from each district) were individually interviewed using a semi-structured questionnaire. The major dairy products produced in the study area include butter, ghee, Ayib, Arera (defatted sour milk), Ergo (naturally fermented sour milk), Zure and Metata Ayib. Among these, two of the traditional dairy products, Zure and Metata Ayib, are unique to the area and have never been reported before. The respondents interviewed claim that these products are of high nutritional values and have therapeutic properties. Many aspects of Zure and Metata Ayib such as physico-chemical properties, microbiological and sensory qualities are unknown. Thus, detailed scientific investigation needs to be conducted in order to verify the claimed nutritional and medicinal properties of these products.